Within‐year changes in Chinese secondary school students' perceived reading instruction and intrinsic reading motivation. (16th August 2014) - Lau, Kit‐ling
Abstract : This study aimed to expand on existing research about motivational change by investigating within‐year changes of adolescents' intrinsic reading motivation and perceived reading instruction among students from different grades and achievement levels. Six hundred and ninety five students from 10 secondary schools in Hong Kong voluntarily completed a questionnaire that measured these two variables at the beginning and near the end of a school year. The study's findings indicated that students' intrinsic reading motivation was generally stable over a school year. A significant increase in the perceived degree of mastery goal structure in reading instruction was observed near the end of the school year. Students' perception of instruction remained a strong and positive predictor of intrinsic motivation after controlling their prior motivation and other background variables. Different factors affecting students' motivational change are discussed to provide insights for promoting their reading motivation and counter the prevalent trend of motivational decline.